PERCEPTION OF THE AI USE: IN UNDERSTANDING ENGLISH ISLAMIC EDUCATION LITERATURES BY ISLAMIC EDUCATION STUDENTS - Guntur Cahyono; Win Listyaningrum Arifin; Purnomo Purnomo (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
Abstract: This study aims to analyze the perception of the use of Artificial Intelligence (AI) in helping Islamic Education students (PAI) at PTKIN in Central Java to understand English-language Islamic education literature. The study used a quantitative approach, a survey method, and analyzed using the Technology Acceptance Model (TAM) modified with Computer Self-Efficacy (CSE) variables. The sample consisted of 100 PAI students from six State Islamic Religious Colleges (PTKIN) in Central Java. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was used to analyze the data. The results showed that Computer Self-Efficacy had a significant effect on Perceived Ease of Use (t = 9.556; p < 0.001) and Perceived Usefulness (t = 5.912; p < 0.001). Perceived Ease of Use had a significant effect on Perceived Usefulness (t = 7.313; p < 0.001) and Attitude Toward Using (t = 5.108; p < 0.001). Perceived Usefulness also significantly influences Attitude Toward Using (t = 8.183; p < 0.001). Furthermore, Attitude Toward Using significantly influenced Behavioral Intention to Use (t = 9.095; p < 0.001), and Behavioral Intention to Use significantly influences Actual System Use (t = 16.280; p < 0.001). However, the effect of Perceived Usefulness on Behavioral Intention to Use is not significant (t = 1.623; p = 0.105). These findings confirm that technology confidence and the ease of use of AI are key factors in AI utilization among PAI students, highlighting important implications for promoting AI adoption in Islamic education contexts.